PENGARUH LINGKUNGAN KELUARGA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS SISWA KELAS VII SMPN 16 SURAKARTA TAHUN AJARAN 2017/2018 - -, Dian Rahmawati -; -, Harini -; -, Jonet Ariyanto Nugroho - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This  study  aims  to  determine  whether  or  not  there  is  (1)  positive  and significant  influence  between  family  environment  variables  and  learning motivation  on  social  studies  learning  outcomes  for  grade  VII  students  of SMPN  16  Surakarta  in  the  academic  year  2017/2018;  (2)  positive  and significant  family  environment  variables  on  social  studies  learning outcomes  for  grade  VII  students  of  SMPN  16  Surakarta  in  the  academic year  2017/2018;  (3)  positive  and  significant  variables  of  learning motivation towards social studies learning outcomes for grade VII students of SMPN 16 Surakarta in the academic year 2017/2018   The  type  of  this  research  is  descriptive  quantitative  with  survey method. The population in this study were seventh grade students of SMPN 16  Surakarta,  amounting  to  162  students  with  sample  of  115  respondents. The  sampling  technique  used  in  this  study  is  Proportionate  Random Sampling  by  lottery.  Data  collection  is  done  by  questionnaire  technique and  documentation  technique.  The  validity  of  the  data  obtained  through tryout  conducted  to  30  respondents.  The  data  analysis  technique  used  is the technique of multiple linear regression analysis.   Based on the result of this research, it can be concluded that: (1) F  test  results  obtained  Fcount  value>  Ftable  (36,023>  3,08)  with probability value <0,05 that is equal to 0,000, so it can be concluded that H0 is rejected and Ha is accepted. It means that there is significant effect of  of    family  environment  variables,  learning  motivation  variables silmutaneously towards student learning outcomes,(2) The results of the t- test  of  family  environment  variables  obtained  the  value  of  tcount>  ttable (2,346>  1,983)  with  a  probability  value  <0,05  that  is  equal  to  0,000  so that  H0  is  rejected  and  Ha  is  accepted.  It  means  that  there  is  significant effect  of    family  environment  variables  partially  toward  student  learning outcomes,(3)  The  results  of  the  t-test  of  learning  motivation  variables obtained tcount> ttable (5.793> 1.983) with a probability value <0.05 that is equal to 0,000, so that H0 is rejected and Ha is accepted. It means that there  is  a  significant  effect  of  learning  motivation  variables  partially toward student learning outcomes.